Preparation of biosilica glass-based porous scaffolds using various elements (Mg-Zn, Mg-Cu, and Sr-Cu) as bioactive glass co-dopants: In vitro bioactivity and biocompatibility behaviors - Ozarslan, Ali Can (SPRINGER HEIDELBERG, 2023)
In the present study, bioactive biosilica glass-based porous scaffolds have been produced by the dual incorporation of Mg, Zn, Sr, and Cu into glasses. Structural analysis indicated that co-dopants resulted in changes in the network connectivity as well as in the oxygen density values of biosilica glass network. Results also showed that scaffolds had suitable pore size range (100-400 mu m) and porosity (82-85%). While the co-incorporation of MgO and CuO resulted in the lowest crystal apatite size (6.5 nm) on the scaffold surface, the co-incorporation of SrO and CuO resulted in highest (9.7 nm) at the end of 28th day in simulated body fluid (SBF). Porous scaffolds showed biocompatible features (up to 100 mg/ml) and had positive impact on cells according to indirect cell study, especially at 25 mg/ml. The results demonstrated that these biocompatible porous scaffolds with appropriate degradation and bioactivity properties are prominent candidates for bone treatment.
Keywords: Bioactive biosilica glasses; Bioactivity behavior; Biocompatibility; Co-incorporation; Porous scaffolds; GEL-DERIVED GLASSES; RICE HUSK ASH; BONE TISSUE; SINTERING TEMPERATURE; MECHANICAL-BEHAVIOR; STRONTIUM; ZINC; SUBSTITUTION; CERAMICS; SILICA; Materials Science